Evaluation of the implementation of International Classification of Diseases, 11th revision for morbidity coding: Rationale and study protocol. (2021) - Golpira, Reza; Azadmanjir, Zahra; Zarei, Javad; Hashemi, Nasim; Meidani, Zahra; Vahedi, Akram; Bakhshandeh, Hooman; Fakharian, Esmaeil; Sheikhtaheri, Abbas
Abstract: International Statistical Classification of Diseases and Related Health Problems, 10th Revision (ICD-10) has been used for many years in many countries to manage health information. The World Health Organization (WHO) will soon replace ICD-10 with the International Classification of Diseases, 11th revision for Mortality and Morbidity Statistics (ICD-11 MMS or ICD-11). The transition to ICD-11 requires the acquisition of the right information for the right policymaking to manage the transitional period. As one of these countries, Iran has initiated a plan to implement ICD-11. The purpose of this paper is to describe the methodologies of our evaluation studies on the implementation of ICD-11 for morbidity coding. We established scientific and executive committees of the study at the Ministry of Health and Medical Education (MOHME) and coordinated our implementation with the WHO. The scientific committee developed the necessary training curriculum in the form of workshops and mentoring courses. We also developed five independent sub-studies with different and related goals to answer the questions considered important by the MOHME and the WHO. The purposes of these sub-studies are to compare the accuracy of coding with ICD-11 and ICD-10, to compare the coding time with ICD-11 and ICD-10, to evaluate the ICD-11 content to cover diagnoses documented in medical records and identify non-covered terms, to evaluate the quality of clinical documentation needed for coding with ICD-11 and the impact of training on clinical documentation, as well as to understand coders' perspectives on barriers, problems, and opportunities for ICD-11 implementation and its utility. During these sub-studies, over 2000 medical records in two teaching and non-teaching hospitals will be evaluated over a period of five months. In this paper, we discussed our model for conducting evaluation studies and the complete methodologies of these studies, the questions that will be answered during the implementation, and the scientific contribution and policy implication of these questions and sub-studies. Because other countries have started or will start implementing ICD-11 soon, they can use our protocol to tailor their pilot implementations concerning their circumstances and local considerations.